Identifikasi Hama Rayap Kelapa Sawit di Desa Simpang Raya Kabupaten Kuantan Singingi - Angga Pramana; A Haitami; Jamalludin Jamalludin (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2018)
Palm oil is one of the fastest growing commodities in the last two decades. Termites are one type of pest in oil palm plantations. This pest is a major pest of young oil palm plantations, especially re-planting in peat areas. The impact is very large, such as a decline is not production. These pests can be growth from seedlings to harvest. This research aims to know the types and characteristics termites in oil palm plantations Simpang Raya, Singingi Hilir, Riau February until June 2016. The method of this research was using descriptive method and field observations. Data were analyzed with descriptive assessment study and using a guidebook used to description pest. The sample were conducted by unload nests in any point sample, when the sample were done in the morning and to identify type termites can use a book. The result showed that the termites attacked in the corner kingdom is the type Coptotermes curvignathus and Macrotermes gilvus. Has often rise after the rainy season this to be supported by conditions of temperature that fits perfectly.